New Insight on the Formation of Sodium Titanates 1D Nanostructures and Its Application on CO2 Hydrogenation - Díaz de León, J. Noé; Rodríguez, Jassiel R.; Rojas, Joel; Esqueda-Barrón, Yasmin; Cardenas, Luis; Ramesh Kumar, Chowdari; Alonso-Nuñez, Gabriel; Fuentes-Moyado, Sergio (Frontiers in Chemistry, 2019)
The aim of this work is focused on the study of a series of non-traditional catalytic nanomaterials to transform greenhouse CO2 gas into added-value products. We found encouraging results of CO2 hydrogenation activity over sodium titanates with different morphologies. The yield to methanol increases with the increase in the Na incorporated in the nanostructures confirming the proposed mechanism. Samples were prepared at different times of hydrothermal treatment (HTT) with NaOH solutions, and these materials were labeled as Ti-nR-x with x as the hours on the HTT. HRTEM initially showed sphere-shaped nanoparticles in the TiO2 commercial nanopowder, increasing the HTT resulted in morphological changes in which the structures passed from nanosheets and finally to nanorods after 30 h. The X-ray diffraction and Raman spectroscopy results indicated the formation of sodium titanates such as Na2Ti3O7 with short Ti O bonds and that Na begins to be incorporated into the distorted TiO6 crystalline structure after 5 h of HTT (until 12 wt%). The crystalline and shape transformation resulted in a significant modification on the textural properties passing from 51 m2.g-1 to 150 m2.g-1 and from a pore volume of 0.12 cm3.g-1 to 1.03 cm3.g-1 for Ti-ref and Ti-nR-30 respectively. We also observed differences in the electronic properties as the bandgap presented a blue shift from 3.16 eV on the TiO2 reference nano-powder to 3.44 eV for the Ti-nR-30 calcined sample. This fact coincides with the presence of a more electron-rich state of the Ti4+ and the formation of negative charge layer induced by the presence of Na+ interlayer cations detected by XPS analysis, at the same this helped us to explain the catalytic activity results.